Determinant of Cash Waqf Nahdatul Ulama (Case of Muslim Students in Indonesia) - Dennis, Dede; Qoyum, Abdul; Sakti, Muhammad Prima (Madania: Jurnal Kajian Keislaman, 2018)
Abstract: Determinant of Cash Waqf Nahdatul Ulama (Case of Muslim Students in Indonesia). Cash waqf is getting popular in some countries because of its flexibility. Due to that, Bank BTN is supporting the cash waqf through releasing an application called “Mobile Wakaf Uang NU BTN” which is able to be downloaded on App Store. This application is in cooperation with LWP-NU. The purpose of this study is to examine the determinant of cash waqf contribution among Muslim students through Mobile Wakaf Uang NU BTN. Attitude, Islamic religiosity, Islamic egalitarianism and perceived are used as independent variable and its intention of Muslim students in Indonesia to contribute to cash-waqf. The sample of this study are 115 Muslim students who applying Mobile Wakaf Uang NU BTN. This study employs Structural Equation Model (SEM) to verify the determinants of cash waqf contribution and the program used is Smart PLS. This study found that religiosity positively influence on attitude, Islamic egalitarianism, and behavioral intention. While, Islamic egalitarianism as a mediating variable positively influence on intention is rejected, because the p-value is more than 5% (0.05). Attitude as a mediating variable has a positive influence on intention and perceived ease of use is accepted and perceived ease of use toward intention has a positive influence. In addition, the interesting result of the study showed that the Islamic egalitarianism does not significantly affect on behavioral intention of Muslim students.